Comparison Between Corticosteroid and Lidocaine Injection in the Treatment of Tennis Elbow: A Randomized, Double-Blinded, Controlled Trial. (February 2018) - Hsieh, Lin-Fen; Kuo, Ying-Chen; Lee, Chia-Cheng; Liu, Ya-Fang; Liu, Yu-Chia; Huang, Vincent
Abstract : Objective: The aim of the study was to compare the effects of corticosteroid injection with lidocaine injection in treating tennis elbow. Design: It is a prospective, double-blinded, randomized controlled trial. Patients with tennis elbow for more than 1 mo were recruited from a hospital-based rehabilitation outpatient clinic. A total of 70 patients were recruited, and 61 patients completed the study. Patients received an injection of either 10 mg (1 ml) of triamcinolone (corticosteroid group, n = 30) or 1 ml of 1% lidocaine (lidocaine group, n = 31). All of the outcome measures were evaluated before the intervention and at 2 wks and 2 mos after treatment. Results: No significant group differences were observed between the corticosteroid and lidocaine groups regarding Patient-Rated Tennis Elbow Evaluation, Disability of the Arm, Shoulder, and Hand, visual analog scale for pain, and grip strength at baseline and at 2 wks and 2 mos after treatment ( P > 0.05). However, within-group comparison showed significant improvement after injection with regard to Patient-Rated Tennis Elbow Evaluation, Disability of the Arm, Shoulder, and Hand, visual analog scale for pain, and grip strength in both groups ( P > 0.05). Conclusions: No differences in the short-term outcomes were found between lidocaine and corticosteroid injection in a small sample of people with tennis elbow with mean duration of 3.8 mos. Abstract : Supplemental digital content is available in the text.